A graphene quantum dot decorated SrRuO3 mesoporous film as an efficient counter electrode for high-performance dye-sensitized solar cells. Issue 34 (17th August 2017) - Liu, Tao; Yu, Kun; Gao, Lina; Chen, Hui; Wang, Ning; Hao, Luhan; Li, Tingxi; He, Hongcai; Guo, Zhanhu
Abstract : The predominant synergic effect of GQDs and SrRuO3 CEs drives faster ion diffusions and electron transfer, thereby contributing to excellent catalytic activity of the SRO–GQD CE towards I3 − reduction. Abstract : Hydrothermally synthesized electrically conductive perovskite strontium ruthenate (SrRuO3 ) nanoparticles were added into a binder solution and then cast onto fluorine doped tin oxide (FTO) glass to form a mesoporous SrRuO3 counter electrode (CE) for dye-sensitized solar cells (DSSCs). The high porosity and large specific surface area of the SrRuO3 CE allows easier and faster diffusion of electrolyte into the pores and involves more triiodide (I3 − ) in the redox reaction, thereby resulting in a higher power conversion efficiency (PCE, 7.16%) than that of our published research on sputtered SrRuO3 film CEs (6.48%). Furthermore, graphene quantum dots (GQDs) endowed with excellent intrinsic catalytic activity and high conductivity were decorated onto the SrRuO3 CE by a dipping technique to form a SRO–GQD hybrid. The synergistic effect of SrRuO3 and GQDs contributes to more active catalytic sites as well as faster ion diffusion and electron transfer than a pristine SrRuO3 CE, thereby resulting in increased electrocatalytic ability towards I3 − reduction. As a result, our fabricated DSSCs based on the optimized SRO–GQD CE achieve an impressive PCE of 8.05%, much higher than that of the reference device assembled with a conventional platinum (Pt) CE (7.44%). The SRO–GQD CE also exhibits an excellent long-term electrochemical stability in I3 − /I − electrolyte. Overall, the SRO–GQD hybrid can be considered as a highly efficient Pt-free CE for practical applications of DSSCs.